Neurocognition and quality of life after reinitiating antiretroviral therapy in children randomized to planned treatment interruption. (24th April 2016) - Ananworanich, Jintanat; Melvin, Diane; Amador, Jose T.R.; Childs, Tristan; Medin, Gabriela; Boscolo, Valentina; Compagnucci, Alexandra; Kanjanavanit, Suparat; Montero, Samuel; Gibb, Diana M.
Abstract : Objective: Understanding the effects of antiretroviral treatment (ART) interruption on neurocognition and quality of life (QoL) are important for managing unplanned interruptions and planned interruptions in HIV cure research. Design: Children previously randomized to continuous (continuous ART, n  = 41) vs. planned treatment interruption (PTI, n  = 47) in the Pediatric European Network for Treatment of AIDS (PENTA) 11 study were enrolled. At study end, PTI children resumed ART. At 1 and 2 years following study end, children were assessed by the coding, symbol search and digit span subtests of Wechsler Intelligence Scale for Children (6–16 years old) or Wechsler Adult Intelligence Scale (≥17 years old) and by Pediatrics QoL questionnaires for physical and psychological QoL. Transformed scaled scores for neurocognition and mean standardized scores for QoL were compared between arms by t -test and Mann–Whitney U test, respectively. Scores indicating clinical concern were compared (<7 for neurocognition and <70 for QoL tests). Results: Characteristics were similar between arms with a median age of 12.6 years, CD4 + of 830 cells/μl and HIV RNA of 1.7 log10 copies/ml. The median cumulative ART exposure was 9.6 in continuous ART vs. 7.7 years in PTI ( P  = 0.02). PTI children had a median of 12 months off ART and had resumed ART for 25.2 months at time of first assessment. Neurocognitive scores were similar between arms for all tests. Physical and psychological QoL scores were no different. About 40% had low neurocognitive and QoL scores indicating clinical concern. Conclusion: No differences in information processing speed, sustained attention, short-term memory and QoL functioning were observed between children previously randomized to continuous ART vs. PTI in the PENTA 11 trial.